An acoustic human-machine front-end for multimedia applications - Herbordt, Wolfgang; Buchner, Herbert; Kellermann, Walter (EURASIP J APPL SIG P, 2003)
A concept of robust adaptive beamforming integrating stereophonic acoustic echo cancellation is presented which reconciles the need for low-computational complexity and efficient adaptive filtering with versatility and robustness in real-world scenarios. The synergetic combination of a robust generalized sidelobe canceller and a stereo acoustic echo canceller is designed in the frequency domain based on a general framework for multichannel adaptive filtering in the frequency domain. Theoretical analysis and real-time experiments show the superiority of this concept over comparable time-domain approaches in terms of computational complexity and adaptation behaviour. The real-time implementation confirms that the concept is robust and meets well the practical requirements of real-world scenarios, which makes it a promising candidate for commercial products. © 2003 Hindawi Publishing Corporation.
Keywords: Frequency-domain adaptive filters; Generalized sidelobe canceller; Hands-free acoustic human-machine front-end; Microphone arrays; Robust adaptive beamforming; Stereophonic acoustic echo cancellation